2021
DOI: 10.1093/plphys/kiab553
|View full text |Cite
|
Sign up to set email alerts
|

The MADS-domain factor AGAMOUS-Like18 promotes somatic embryogenesis

Abstract: AGAMOUS-Like 18 (AGL18) is a MADS domain transcription factor (TF) that is structurally related to AGL15. Here we show that, like AGL15, AGL18 can promote somatic embryogenesis (SE) when ectopically expressed in Arabidopsis (Arabidopsis thaliana). Based on loss-of-function mutants, AGL15 and AGL18 have redundant functions in developmental processes such as SE. To understand the nature of this redundancy, we undertook a number of studies to look at the interaction between these factors. We studied the genome-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 78 publications
2
30
1
Order By: Relevance
“…This would be consistent with AGL15 recruitment of histone deacetylase complexes to repress gene expression (discussed further below) (Hill et al, 2008 ). Neither SERRATE nor HEN1 were found as targets in our ChIP studies (Zheng et al, 2009 ; Paul et al, 2021 ).…”
Section: Agl15 Directly Binds Genes Encoding Micro-rnascontrasting
confidence: 56%
See 4 more Smart Citations
“…This would be consistent with AGL15 recruitment of histone deacetylase complexes to repress gene expression (discussed further below) (Hill et al, 2008 ). Neither SERRATE nor HEN1 were found as targets in our ChIP studies (Zheng et al, 2009 ; Paul et al, 2021 ).…”
Section: Agl15 Directly Binds Genes Encoding Micro-rnascontrasting
confidence: 56%
“…These include a set of WRKY, NAC, and bZIP TFs that have been associated with dedifferentiation (Grafi et al, 2011 ). A more recent ChIP-seq study for Arabidopsis AGL15 revealed that regulatory regions corresponding to genes encoding nearly all of these TFs are directly bound by AGL15, which seems quite extraordinary (Paul et al, 2021 ). When comparing the percentage of genes encoding these TFs bound by AGL15 to the percentage of genes bound overall compared to the whole genome, a significant enrichment in the dedifferentiation-related (DD) TFs potentially directly regulated by AGL15 is observed ( Table 1 ).…”
Section: Gene Regulation By Agl15 During Somatic Embryogenesismentioning
confidence: 99%
See 3 more Smart Citations